Christ-centered worship : letting the Gospel shape our practice - Chapell, Bryan (Grand Rapids, Mich. : Baker Academic, 2009)
The church's worship has always been shaped by its understanding of the gospel. Here Bryan Chapell provides churches with a Christ-centered understanding of worship to enable them to transcend the traditional/contemporary worship debate and unite in ministry and mission priorities. --from publisher description.
Gospel worship -- The Gospel of structure -- The Roman story -- Luther's story -- Calvin's story -- Westminster's story -- The modern story --
Includes bibliographical references and index.
Keywords: Worship; Public worship